PHYSICAL EDUCATION AS A LANGUAGE: BASIS FOR REPOSITIONING IN SCHOOL CURRICULUM (Fiep Bulletin - online, 2014)
Some proposals of Physical Education curriculum impose to students the appropriation of a certain body language already produced and standardized. In this vision, teachers do not concern themselves in performing a reading of the linguistic repertory of the social group with which he works. This way, transmits a performance ideology, due to the predominant interest with an expression incorporation considered ideal and disqualifies any cultural production processes of other groups. Once the body culture of movement embraced general themes to be worked in school, their curriculums could, initially, involve itself with a body language deriving from children in school and try to understand, explain and systemize them. The purpose of this study was to analyze body language systemizing through the Semiotic comprehension, searching to present basis for its repositioning in school curriculum. The reasons that guided to the Semiotic study are related to the understanding that school Physical Education, in its cultural approach, can search for basis in language science, considering that critical theories of Education promote school as the meeting place of cultures and Physical Education as a space of recognition, to give new meanings and increasing of the motor culture. The methodological guiding was based on an exploratory study and data analysis allow us to infer that Semiotic philosophical archeology provide the basis to understand body language as one of the body culture manifestation characteristics. Therefore, the contribution of the investigations imply in a reorganization of the critic Physical Education educative process and provides subsides for a reorganization in school practice.
Keywords: Physical Education; Body Language; Curriculum